Future Prospects and Challenges in Additive Manufacturing for Complete Dentures: A Narrative Review - Mariya Dimitrova; Angelina Vlahova; Yavor Kalachev; Rada Kazakova; Saverio Capodiferro (MDPI AG, 2023)
The utilization of computer-assisted design and computer-assisted manufacturing (CAD/CAM) techniques in the creation of complete dentures (CDs) has piqued the interest of many people. This article seeks to provide a comprehensive, critical, and objective analysis of the current knowledge of CDs and related technology. The aim of this study is to assess existing literature concerning 3D-printed complete dentures, covering aspects like innovative biomaterials, manufacturing methods and processes, workflow, and clinical effectiveness. The design of the current study included an initial review of 172 titles, an appraisal of abstracts, and finally a selection of articles for rigorous textual analysis. Inconsistencies discovered throughout the selection process were amicably resolved through discourse, culminating in the identification of 65 items. The publications retrieved from a thorough search of the PubMed, Scopus, and Embase databases spanned the years 1994 to 2023. Contemporary digital technology provides evident advantages, but its successful incorporation necessitates meticulous preparation. In the realm of dental healthcare, the digital workflow showcases versatility and a range of applications.